Caracterização da concentração industrial no Rio Grande do Norte entre os anos 2000 e 2010. - Azevedo, Sylvester Stallone Pereira de (2012)
This study aims to characterize the levels and patterns of concentration of industrial activity in the state of Rio Grande do Norte in the period between 2000 and 2010. For this there will be the calculation of the indices of spatial correlation Global Moran's I and local (LISA) defined by Anselin (1995) between the territorial subdivisions of the state - microregions. It was identified that the state only has clusters of positive spatial correlation in the manufacturing industry and the sectors of capital, labor and natural resource intensive. It was also observed that the resource sector is less concentrated in both years considered polar and that all sectors have experienced decentralization of industrial activities except for the labor-intensive sector, which takes the place of more concentrated industry in 2010, this place occupied by the capital-intensive sector in 2000. In the estimation of the model say that the influence of the variables defined in the theory of growth was observed that the small amount of micro state not allowed to obtain a model very consistent. This suggested the estimation of models considering the variables individually, allowing better understand the influence that the wages paid to the worker, the average size of establishments, the distances of the micro and the capital share in manufacturing employment that each state has in the micro affect growth of such participation, indicating the agglomeration tendencies. The results are consistent with the arguments presented in the New Economic Geography and the empirical studies that have been done to test them.